2023
DOI: 10.11647/obp.0366
|View full text |Cite
|
Sign up to set email alerts
|

Ethics of Socially Disruptive Technologies

Abstract: Technologies shape who we are, how we organize our societies and how we relate to nature. For example, social media challenges democracy; artificial intelligence raises the question of what is unique to humans; and the possibility to create artificial wombs may affect notions of motherhood and birth. Some have suggested that we address global warming by engineering the climate, but how does this impact our responsibility to future generations and our relation to nature? This book shows how technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 195 publications
0
2
0
Order By: Relevance
“…This inevitably comes with transformations of traditional ethical concepts. Elsewhere in research, it has already been shown that with the advent of emerging technologies like robots, our ethical concepts are being disrupted and transformed (Van de Poel et al, 2023a;Van de Poel et al, 2023b;Hopster et al, 2023).…”
Section: Consequences For Robot Ethicsmentioning
confidence: 99%
“…This inevitably comes with transformations of traditional ethical concepts. Elsewhere in research, it has already been shown that with the advent of emerging technologies like robots, our ethical concepts are being disrupted and transformed (Van de Poel et al, 2023a;Van de Poel et al, 2023b;Hopster et al, 2023).…”
Section: Consequences For Robot Ethicsmentioning
confidence: 99%
“…In other words, AI may be a disruptive technology when it comes to other sociotechnical systems and society (Hopster, 2021;Van de Poel et al, 2023). AI may add new elements to energy systems allowing, for example, forms of real-time trading of energy, or optimizing energy delivery through the net.…”
Section: The Added Value Of a Sociotechnical Systems Approachmentioning
confidence: 99%